New Cybersecurity Challenges: Digital Transformation and the Political Implications of their Implementation - Anna Sisoyan (Journal of Political Science: Bulletin of Yerevan University)
The purpose of this article is to analyze modern challenges in the field of cybersecurity and mechanisms for countering cyber threats, assess the problems our country faces in this area, and identify possible solutions. To achieve this goal, the article studies the basic concepts related to cyberspace, considers real examples of cyber attacks recorded in recent years, and studies the experience, legislative and institutional framework of the leading countries in this area. In this context, the author highlights the structural similarities and differences of the countries in question. The relevance of this article is due to the analysis of new challenges to cybersecurity and the growing scale of application of information technologies in all spheres of human political activity. In the era of digitalization, information is acquiring the status of the most important object, a strategic resource of both the state and any management structure in the political management system. In this context, the relevance of the research topic is manifested in the development of the concept of a knowledge and information society developing on the basis of modern information and communication technologies. Information as a strategic resource requires a special state attitude not only in terms of its development and accumulation, but also protection. The article also analyzes the development of new information technologies, which causes an increase in the technological gap between the increasingly complex requirements for information resource security indicators in all countries and the capabilities of information technologies and software and hardware used to ensure information security.